PENGARUH PERENCANAAN SDM, REKRUTMEN, SELEKSI DAN PENEMPATAN TERHADAP KINERJA KARYAWAN PADA PT. EJUKHA KOTA BENGKULU - Permatasari, Dea Indah (UM. Bengkulu, 2025)
Employee performance in companies operating in the contracting, construction and property sectors is influenced by various factors, including HR planning, recruitment, selection and placement. This research aims to analyze the influence of HR planning, recruitment, selection and placement on employee performance at PT. Ejukha, Bengkulu City. The research method is quantitative with a survey approach. The research population was all employees of PT. Ejukha, Bengkulu City. The total sample was 40 people. Data was collected through questionnaires distributed to company employees using t-test technique variable Human Resource Planning t-value = 4.104> t-table value = 1.688 or Sig = 0.000 <α value = 0.05. Recruitment t-value = 4,000> t-table value = 1,688 or Sig = 0.000 <α value = 0.05. Selection t-value = -8.872> t-table value = 1.688 or Sig = 0.000 <α value = 0.05. Placement t-value = 19.784> t-table value = 1.688 or Sig = 0.000 <α value = 0.05. The research results show that the influence of HR planning, recruitment, placement has a positive and significant effect on employee performance. This means that the higher the HR planning, recruitment and placement, the more employee performance will improve. Meanwhile, selection has a negative and significant effect on employee performance, which means that increasing company selection will have an impact on decreasing employee performance. This research confirms that to improve HR planning, recruitment, selection and placement of employee performance in order to achieve company success. Keywords: HR Planning, Recruitment, Selection, Placement, Employee Performance